Mobile services in the networked economy - Vesa, Jarkko, 1964-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
The mobile services industry is going through a major transformation, which challenges many of the basic assumptions behind the existing business models. As the business paradigm shifts from voice-centric to data-centric mobile services, the ways of analyzing the industry need to evolve as well. This book provides insight into the structure and dynamics of the mobile services industry by combining novel ideas from complexity theory, from research on vertical integration strategies, and from theories of networked organizations. These ideas and theories are then applied to the context of three different types of mobile services markets in Japan, Finland and the UK. The case analyses demonstrate how the three markets are currently going through very distinct phases of evolution in a continuum between two very different kinds of business environments. The analysis of the mobile services industry presented in this book will help the reader not only to understand the logic behind the way the industry looks today, but also to foresee possible future trends in the development of a given mobile services market.
Anatomy of the Mobile Services Industry -- Towards a Networked Economy -- Dynamic Boundaries and Vertical Integration -- Web or Chains -- Networks, Ecosystems and Clusters -- Mobile Services in Japan -- European Mobile Services Industry -- Mobile Services in Finland -- Mobile Services in the UK -- Mobile Markets vs. Mobile Ecosystems -- Mobile Services in a Networked Economy.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 7, 2010).
Keywords: Cell phone equipment industry; Cell phone systems; Mobile communication systems; Electronic books